Pengaruh Musik terhadap Tingkat Kecemasan Mahasiswa Kedokteran dalam Menghadapi Ujian Modul - Perkasa, Octaviannus N.; Munayang, Herdy; Kaunang, Theresia M. D. (Medical Scope Journal, 2025)
Abstract: Anxiety is a common emotional response that can negatively affect academic performance. Medical students often face high-pressure academic environments, especially during module exams, which can impact their mental well-being. Music has been shown to have therapeutic effects that may reduce anxiety levels. This study aimed to analyze the effect of music on the anxiety levels of medical students at Sam Ratulangi University during module examinations. This was a mixed-method study with a sequential explanatory design. The quantitative phase involved a cross-sectional observational analysis using the Zung Self-Rating Anxiety Scale (SAS) questionnaire with 202 respondents. The qualitative phase involved in-depth interviews with ten selected students. Data were analyzed using the Mann-Whitney test for non-normal data. The results showed that most respondents listened to music (74.8%), with pop music being the most preferred genre. Mild anxiety levels were more prevalent among students who listened to music (40.6%) compared to those who did not. The Mann-Whitney test showed a significant difference in anxiety levels between students who listened to music and those who did not (p<0.05). In conclusion, listening to music, particularly slow-tempo music, significantly reduces students’ anxiety levels during module exams. This strategy can be adopted as a simple and effective anxiety management method. Keywords: music; anxiety; medical students; module exams Abstrak: Kecemasan merupakan respons emosional umum yang dapat berdampak pada kemampuan akademik. Mahasiswa kedokteran sering mengalami tekanan tinggi dalam lingkungan akademik, terutama saat menghadapi ujian modul, yang dapat memengaruhi kesejahteraan mental. Musik diketahui memiliki efek terapeutik yang berpotensi mengurangi tingkat kecemasan. Penelitian ini bertujuan untuk menganalisis pengaruh musik terhadap tingkat kecemasan mahasiswa kedokteran Universitas Sam Ratulangi dalam menghadapi ujian modul. Jenis penelitian ialah mixed method dengan desain penelitian sequentioal explanatory. Tahap kuantitatif dilakukan dengan analisis observasional potong lintang menggunakan kuesioner Zung Self-Rating Anxiety Scale (SAS) pada 202 responden. Tahap kualitatif menggunakan wawancara mendalam pada sepuluh mahasiswa terpilih. Analisis data dilakukan menggunakan uji Mann-Whitney. Hasil penelitian menunjukkan sebagian besar responden mendengarkan musik (74,8%), dengan jenis musik pop sebagai pilihan terbanyak. Tingkat kecemasan ringan lebih banyak dialami oleh mahasiswa yang mendengarkan musik (40,6%) dibandingkan yang tidak mendengarkan musik. Hasil uji Mann-Whitney menunjukkan perbedaan bermakna antara tingkat kecemasan mahasiswa yang mendengarkan musik dan yang tidak (p<0,05). Simpulan penelitian ini ialah mendengarkan musik, terutama dengan tempo lambat, dapat menurunkan tingkat kecemasan mahasiswa secara bermakna saat menghadapi ujian modul. Strategi ini dapat diadopsi sebagai metode manajemen kecemasan yang sederhana dan efektif. Kata kunci: musik; kecemasan; mahasiswa kedokteran; ujian modul